Odpowiedzi

2010-01-26T19:13:18+01:00
3. zapisz w jak najprostszej postaci
3(2x - 1) +4(1- x) = 6x - 3 + 4 - 4x = 2x + 1
2(7x + 5) - 6(x - 2) = 14x + 10 - 6x + 12 = 8x + 22
-2x(8 - x) - 5(x² + 3x) = -16x + 2x² - 5x² - 15x = -31x - 3x²
2 1 2
Najlepsza Odpowiedź!
2010-01-26T19:22:39+01:00
E.(x² + x - 1) : (-⅙) = (x2 + x - 1) * (-6) = -6x^2 - 6x +6
f.(2,5x² - 0,5x + 1) : 5 = 0,5x^2 - 0,1x + 1/5

3(2x - 1) +4(1- x)= 6x-3+4-4x = 2x+1
2(7x + 5) - 6(x - 2)= 14x+10-6x+12= 8x+22
-2x(8 - x) - 5(x² + 3x)= -16x+2x^2 - 5x^2-15x = - 31x - 3x^2
6 2 6